CHARACTERIZATION OF TETRACYCLINE-RESISTANT STAPHYLOCOOCUS AUREUS ISOLATED FROM BOVINE MASTITIS IN KHARTOUM STATE, SUDAN - El Zubeir, El Zubeir; E.M, I.; Kiessling, Kiessling; S, S; Kutzer, Kutzer; Wieler, P; M, L.; O.A. O. , El Owni1 (Journal of Veterinary Medicine and Animal Production, 2022)
Thirty four strains of Staphylococcus aureus, isolated from mastitic milk samples and the cow fences in Sudan were used for the polymerase chain reaction (PCR) assay (arbitrary primed PCR), during the present study. The PCR differentiated the isolates into 3 groups, of more than 90% similarity within each. However all the isolates showed more than 70% similarity with each other. Twenty seven (79.41%) of those isolates were tetracycline and deoxocycline resistant. However all the isolates showed susceptibility to minocycline. Plasmids (1-3) were detected in 30 (88.24%) of Staphylococcus aureus isolates. The PCR products of the plasmid DNA and Southern blot hybridization proved that the resistance was due to tet K gene. Endonuclease restriction enzymes (Hind III), when used to cut the plasmid DNA at the restriction site of tet K gene in tetracycline resistant S. aureus isolates, differentiated the isolates carrying the tet K determinants into 4 groups. In one of them the tet K gene was found to be pST S14, while the other three groups carried tet K gene from pT181. Amplification of all products were analysed by electrophoresis in agrose gels (0.8-1.2%) and detected by staining them with or without ethidium bromide. The present study concluded that tet K gene is the common responsible gene for transferring tetracycline resistance among the S. aureus isolated from mastitis –infected cows in Sudan. Further detailed studies are needed to evaluate and estimate the risk and role of antibiotics misuse in veterinary practices